(untitled) (The Research of Medical Science Review, 2025)
Background: The nursing profession faces significant challenges globally, with work-related adversities increasingly affecting nurses' mental health and performance. Failure to adapt and cope with challenges like increased workload, staff shortages, lack of appreciation, and workplace abuse can result in mental health problems among nurses. The World Health Organization has identified job-related stress as a major global concern affecting individuals' mental wellbeing. Resilience plays a protective role in maintaining nurses' mental health and mitigating the effects of work-associated stress. While nurses in Pakistan face similar challenges as their global counterparts, limited research exists on resilience levels and associated factors in this context. Purpose: This study aimed to determine the level of resilience and identify factors associated with resilience among nurses working in a public tertiary care hospital in Islamabad, Pakistan. The research sought to understand both the current state of nurses' resilience and the key factors that influence it within the Pakistani healthcare context. Methodology: An analytical cross-sectional study design was employed at a public tertiary care hospital in Islamabad with 854 registered nurses. Data was collected from 323 nurses through simple random sampling, achieving a 94% response rate. The study utilized two validated instruments: the Connor Davidson Resilience Scale (CD RISC-25) to measure resilience and the Perceived Stress Scale (PSS-10) to assess stress levels. The CD RISC-25 measured resilience across seven domains: hardiness, coping, flexibility, purpose, optimism, self-efficacy, and regulation of emotions. Content validity was established through expert panel review, with both instruments showing high validity indices. Data analysis included descriptive statistics and ordinal logistic regression to identify factors associated with resilience. Results: The study revealed that the majority of nurses demonstrated moderate levels of resilience (47.7%), while 26.3% showed low resilience and 26% exhibited high resilience. The mean perceived stress score was 20.3 (±5.7), indicating moderate stress levels. Significant associations were found between resilience and several key factors: perceived stress (p<0.001), physical abuse at the workplace (p=0.025), social support from family and friends (p=0.005), mental health status (p<0.001), and support for household chores (p=0.04). The regression model demonstrated good fit and explained 23.7% of the variance in resilience levels. The study also identified concerning rates of workplace abuse, with 39% of participants reporting various forms of abuse including verbal (35.9%), psychological (32.2%), and physical (13.3%) from patients, their families, and colleagues. Conclusion: The findings highlight that nurses' resilience is significantly influenced by both workplace factors and psychosocial support systems. The predominance of moderate resilience levels suggests room for improvement through targeted interventions. The study underscores the importance of creating safe working environments and providing organizational support to enhance nurses' resilience. Mental health support through resilience training programs and education appears crucial for improving nurses' adaptive capabilities. Implications: Healthcare organizations need to implement comprehensive support systems that address workplace stress and safety while promoting mental wellbeing among nurses. This includes developing clear policies for handling workplace conflicts, ensuring adequate staffing levels, and establishing formal mentoring programs. The findings suggest that enhancing social support systems and addressing work-life balance could significantly improve nurses' resilience. Future research should explore these relationships through longitudinal and multi-center studies to better understand causality and develop effective interventions. Strengths and Limitations: The study's strengths include its novel contribution to understanding resilience in Pakistan's healthcare context, high response rate, and use of internationally validated tools. However, the single-study setting may limit generalizability, and self-reported data may be subject to reporting bias. Despite these limitations, the findings provide valuable insights for improving nurses' resilience in healthcare settings.